2023
DOI: 10.1097/ta.0000000000004100
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of timing to rib fixation in patients with traumatic brain injury: A nationwide analysis

Emanuele Lagazzi,
Dias Argandykov,
Amory de Roulet
et al.

Abstract: BACKGROUND Early surgical stabilization of rib fractures (SSRF) is associated with improved inpatient outcomes in patients with multiple rib fractures. However, there is still a paucity of data examining the optimal timing of SSRF in patients with concomitant traumatic brain injury (TBI). This study aimed to assess whether earlier SSRF was associated with improved outcomes in patients with multiple rib fractures and TBI. METHODS We performed a retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…A previous study has shown that early SSRF was associated with a shorter operating room duration [4], suggesting that patients receiving early procedures may benefit from a reduced duration of anesthesia associated with the SSRF procedure and/or reduced procedural complexity. Recent trials have demonstrated improved outcomes in patients with rib fracture as well, including decreased length of stay and ICU length stay [13]. As such, the findings of this study further reaffirm our understanding of the benefits of early rib fixation.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A previous study has shown that early SSRF was associated with a shorter operating room duration [4], suggesting that patients receiving early procedures may benefit from a reduced duration of anesthesia associated with the SSRF procedure and/or reduced procedural complexity. Recent trials have demonstrated improved outcomes in patients with rib fracture as well, including decreased length of stay and ICU length stay [13]. As such, the findings of this study further reaffirm our understanding of the benefits of early rib fixation.…”
Section: Discussionsupporting
confidence: 76%
“…ISS score was also estimated using ICD-10 codes using the open-access program ICDPIC-R [10,11]. ISS was further categorized into mild (≤8), moderate (9)(10)(11)(12)(13)(14)(15), severe (16-25), and profound (≥25) [12]. The mechanism of injury was categorized as motor vehicle traffic (EXT007) or other using external cause of injury codes.…”
Section: Study Populationmentioning
confidence: 99%
“…24 Given the significant role of armed conflict in contemporary history, it is imperative to address the sequelae of war-related injuries through efficient, low-complication surgical strategies. 29 Amid increasing rates of amputation, there is a growing emphasis on postoperative care that extends beyond mere limb replacement with prosthetics. 30–32 In this realm, the OI method stands out as a potentially viable long-term rehabilitation strategy for individuals who have undergone upper limb amputations.…”
Section: Discussionmentioning
confidence: 99%
“…Timely diagnosis of traumatic chest wall fractures is a crucial component to avoid delays in treatment and poor patient outcomes. 6 We commend the authors for tackling an impactful problem with the potential to improve diagnostic chest X-ray accuracy and reduce potentially avoidable radiation exposure for patients. The use of computer vision models for diagnostic radiology use cases has exploded.…”
Section: Joshua Aaron Villarreal Joseph D Forrestermentioning
confidence: 99%